Efficient Market Hypothesis Analysis on the Indonesian Stock Exchange on the Asean Stock Market - Daniel Fernando Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the performance of Indonesia Stock Exchange to ASEAN stock market during the period 2018-2022. The technique of determining the sample using purposive sampling method and 6 countries as samples are Indonesia, Singapore, Malaysia, Vietnam and Philippines. Hypothesis testing in this study used Descriptive Statistics Analysis, Test Run and Kolomogorov Smirnov with a significance level of 0.05. Test results show that: (1) Indonesia Stock Exchange has the highest efficient rating in ASEAN stock market (2) ASEAN Stock Exchange effect on Indonesia Stock Exchange. (3) The Indonesia Stock Exchange has a stock return pattern that fluctuates normally in the ASEAN stock market.